Association of Acinetobacter baumannii EF-Tu with Cell Surface, Outer Membrane Vesicles, and Fibronectin. (15th May 2012) - Dallo, Shatha F.; Zhang, Bailin; Denno, James; Hong, Soonbae; Tsai, Anyu; Haskins, Williams; Ye, Jing Yong; Weitao, Tao
Abstract : A conundrum has long lingered over association of cytosol elongation factor Tu (EF-Tu) with bacterial surface. Here we investigated it with Acinetobacter baumannii, an emerging opportunistic pathogen associated with a wide spectrum of infectious diseases. The gene for A. baumannii EF-Tu was sequenced, and recombinant EF-Tu was purified for antibody development. EF-Tu on the bacterial surface and the outer membrane vesicles (OMVs) was revealed by immune electron microscopy, and its presence in the outer membrane (OM) and the OMV subproteomes was verified by Western blotting with the EF-Tu antibodies and confirmed by proteomic analyses. EF-Tu in the OM and the OMV subproteomes bound to fibronectin as detected by Western blot and confirmed by a label-free real-time optical sensor. The sensor that originates from photonic crystal structure in a total-Internal-reflection (PC-TIR) configuration was functionalized with fibronectin for characterizing EF-Tu binding. Altogether, with a novel combination of immunological, proteomical, and biophysical assays, these results suggest association of A. baumannii EF-Tu with the bacterial cell surface, OMVs, and fibronectin.